The Effect of Temperature on the Electrical Characteristics of Nanofluids Based on Palm Oil - Pichai Muangpratoom (Journal of Engineering and Technological Sciences, 2021)
This study sought to apply nanotechnology to develop the electrical characteristics of palm oil. Experiments were conducted using three types of nanoparticles: zinc oxide (ZnO), titanium dioxide (TiO2), and barium titanate (BaTiO3). The nanofluid samples were prepared by mixing the nanoparticles with palm oil using various processes. In the first scenario, a combination of palm oil with nanoparticles at 0.01 vol% was created, while the next sample had 0.03 vol% of nanoparticles. The samples were then fully dispersed using a magnetic stirrer, followed by ultrasonic dispersal in order to ensure homogeneity of the nanofluid. The electrodes were set 2.5 mm apart and the test was performed six times on each test sample in compliance with the IEC 60156 standard. The voltage breakdown characteristics were recorded for each of the liquids at temperatures varying from 35 °C to 90 °C. The results showed that for the palm oil samples containing nanoparticles, the voltage breakdown was greater than for the samples containing unmodified palm oil.